2015
DOI: 10.12963/csd.15267
|View full text |Cite
|
Sign up to set email alerts
|

Category Norms for Korean Adults Age 55 to 74

Abstract: This study seeks to provide preliminary data on the production frequency and typicality of noun exemplars by semantic category for Korean adults age 55 to 74. Methods: A total of 401 individuals participated in the study. The study was divided into two parts. In experiment 1 (N= 220), the subjects were given generative naming tasks from ten categories: clothing, kitchen utensils, personal belongings, vegetables, furniture, transportation, school supplies, electronic devices, flowers, and animals. In experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…It is clear from studies reporting descriptive data of multiple SF tasks that there are stark discrepancies in the number of legal words produced by healthy subjects across different semantic categories. Typically, adult healthy subjects produce the most words on animal fluency, while productivity on other semantic categories may be reduced by more than twofold (Bosanac et al, 2017; Gabrić & Vandek, 2021a; Jebahi et al 2020, 2021; Kim et al, 2015; Moreno-Martínez et al, 2017; Vicente et al, 2021). For example, Jebahi et al (2020) reported that subjects produced 18 words on average on animal fluency but less than ten on the categories accessories, tools, transportation means, furniture , and sports .…”
Section: Introductionmentioning
confidence: 99%
“…It is clear from studies reporting descriptive data of multiple SF tasks that there are stark discrepancies in the number of legal words produced by healthy subjects across different semantic categories. Typically, adult healthy subjects produce the most words on animal fluency, while productivity on other semantic categories may be reduced by more than twofold (Bosanac et al, 2017; Gabrić & Vandek, 2021a; Jebahi et al 2020, 2021; Kim et al, 2015; Moreno-Martínez et al, 2017; Vicente et al, 2021). For example, Jebahi et al (2020) reported that subjects produced 18 words on average on animal fluency but less than ten on the categories accessories, tools, transportation means, furniture , and sports .…”
Section: Introductionmentioning
confidence: 99%